A Visual Aided DSS Prototype Development to Mitigate the Flood Hazards - Nasly, Mohamed Ali; Saher, Faisal Nadeem (Scientific & Academic Publishing, 2013)

(untitled)
Flood hazards caused by extreme rain events or unplanned watersheds is a problem and it has become a growing concern under impact of climate change. There is a dire need to develop new paradigm to combat flood hazards and operational decision-making process. Effective decision is a challenge, in a context to select best-suited option for mitigation. The general objective of this paper is to propose a visual aided decision support platform providing an ease but acceptable level of strategy. Presented prototype includes modelling and GIS based visual aids. A study of Pahang River in Malaysia conducted, to explain the applications of the prototype. This study affirms two major conclusions: First, there is great potential to adopt the proposed methodology at a level of decision-making authorities, leading to selection of actual measures for flood mitigation. Second, integration of model, Water Evaluation and Planning (WEAP), Global Mapper and GIS proved as a salient feature of Decision Support System as visual aided scenario generation. This paper has given an account of and the reasons for the use of prototype for flood hazards.